Energy consumption, energy intensity, economic growth, FDI, urbanization, PM2.5 concentrations nexus - Bildirici, Melike; Kayikci, Fatma Coban (SPRINGER, 2024)
This paper investigated the dynamic and causal relationship among energy intensity, economic growth, urbanization, energy consumption, FDI, and PM2.5 in 1995-2019 period for China, India, Germany, Canada, USA and United Kingdom countries through Panel Fourier Bootstrapping ARDL (PFBARDL) model and Panel Fourier causality test. According to PFBARDL results, the evidence of cointegration between the variables was detected. In the PFBARDL model, the error correction coefficient is determined as -0.169. Results showed that there is a bidirectional causality between economic growth and PM2.5 release, between fdi and PM2.5 release, between energy intensity and PM2.5 release. Rising economic growth, energy consumption structure, and urbanization will have an adverse effect on PM2.5 concentrations. Policy makers must carefully balance the connection between mitigation of PM2.5 and diminishing energy consumption, and increasing economic growth, urbanization, and energy intensity for determining policies to control PM2.5 concentrations. Thus, in order to reduce PM2.5, the governments must explore a new economic pattern to decouple the linkage between PM2.5 and economic growth.
Keywords: Energy intensity; Economic growth; Urbanization; Energy consumption; FDI; PM2 5; PARTICULATE MATTER PM2.5; CO2 EMISSIONS; AIR-QUALITY; DECOMPOSITION ANALYSIS; OECD COUNTRIES; CHINA; POPULATION; IMPACTS; DETERMINANTS; ENVIRONMENT; Science & Technology - Other Topics; Environmental Sciences & Ecology